Review of directed energy deposition additive manufactured printed specimens - Yusuf Bin Mohd Azawan (Nanyang Technological University, 2024)
This Final Year Project (FYP) paper presents a comprehensive study on the fatigue behaviour of Directed Energy Deposition specimens on these 5 commonly used materials - Stainless Steel 316L (SS316L), Titanium Alloy (Ti-6Al-4V), Aluminium Alloy (AlSi10Mg), Inconel 625 (IN625), Inconel 718 (IN718). The focus is on two key factors influencing fatigue life, which is process parameters (including post-processing) and microstructure.